2012
DOI: 10.1590/1414-431x20122586
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of protein-energy malnourished patients in a Brazilian university hospital

Abstract: Protein-energy malnutrition (PEM) is a treatable disease with high prevalence among hospitalized patients. It can cause significant increases in the duration of hospitalization and costs. PEM is especially important for health systems since malnourished patients present higher morbidity and mortality. The objective of the present study was to assess the evolution of nutritional status (NS) and the effect of malnutrition on clinical outcome of patients at a public university hospital of high complexity in Brazi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
0
9
0
3
Order By: Relevance
“…However, due to the influence of the commitment of the nutritional status in the clinical evolution of individuals exposed to disease 4,16,17 some investigators have reported the supply of energy and protein in quantities greater than those calculated nutritional needs. In studies carried out by several investigators 7,[18][19][20] the general and specialized oral diets presented energy supply around 1.900 to 2.700 kcal/day, i.e., higher values than the calculated energy for patients included in these studies (1.400 to 2.200 kcal/day).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, due to the influence of the commitment of the nutritional status in the clinical evolution of individuals exposed to disease 4,16,17 some investigators have reported the supply of energy and protein in quantities greater than those calculated nutritional needs. In studies carried out by several investigators 7,[18][19][20] the general and specialized oral diets presented energy supply around 1.900 to 2.700 kcal/day, i.e., higher values than the calculated energy for patients included in these studies (1.400 to 2.200 kcal/day).…”
Section: Discussionmentioning
confidence: 99%
“…Since in a previous study developed in our hospital it was demonstrated that 33.2% of patients that were evaluated within the first 48 hours of admission presented protein-energy malnutrition 4 the identification of such a prolonged overnight fasting period is highly worrying. In accordance with these considerations, in a study developed by Söderström et al 23 analyzing elderly hospitalized individuals (n = 1771) it was demonstrated that inadequate dietary habits including prolonged overnight fasting (> 11h) increased the risk of malnutrition 23 .…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…As a result of this stress response, critically ill patients are bound to develop protein and energy deficits, added by total or partial inability of oral feeding. In order to prevent nutrition deficits related with the morbidity and mortality of hospitalized patients (2) and their associated worse clinical outcomes, enteral nutrition (EN) is the recommended first-line therapy for critically ill patients (3).…”
Section: Introductionmentioning
confidence: 99%
“…These considerations are consistent with the results of a study recently published. Using a logistic model, the investigators demonstrated that malnourished patients had a significantly increased risk of developing infectious complications compared with well-nourished patients (odds ratio=19.80) 14 .…”
mentioning
confidence: 99%